Work accident reporting in coal mining, Indonesia: A systematic literature review - Sultan, Muhammad; Setyadi, Djoko; Ramdan, Iwan Muhamad; Haviluddin, Haviluddin; Hidayati, Tetra (Periodicals of Occupational Safety and Health, 2023)
Background: Work accidents and work-related diseases are still considered as nightmares in Indonesia, especially in the coal mining sector. Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan (Social Security Agency for Employment) reported that there were as many as 234,370 cases of work accidents and work-related diseases in 2021, where the mining sector contributed as many as 6,565 cases. This study aims to present the analysis and synthesis of various research to provide solution recommendations in the management of accident reporting which are suitable to the characteristics of coal mining in Indonesia. Method: This study is a Systematic literature review of a number of studies sourced from Elsevier, Science Direct, Google Scholar, Pubmed, Proquest, DOAJ, Perpusnas RI, Garuda, and other sources. Results: Based on the literature analysis, it is found out that reporting management based on digitalization either in the form of website portal or application is a solution to optimize the effort to control work accidents and work-related disease in coal mining. Conclusion: This reporting system can be applied in coal mining in Indonesia.